PROFILING EMPLOYEE GREEN BEHAVIOR IN A GOVERNMENT INSTITUTIONS OF JAMBI PROVINCE - Hazimah Azzahra; Beny Rahim; Nurul Hafizah (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the comprehensive implementation of Employee Green Behavior (EGB) among government employees through the multidimensional framework of the Green Five Taxonomy. The research method utilized is a quantitative approach with a descriptive design, involving civil servants and outsourced personnel as respondents. The results indicate that, generally, employees' pro-environmental behavior remains at a moderate compliance level. Based on the dimensional analysis, daily resource-saving activities emerge as the most universal green behavior, successfully adopted as a basic office routine driven by formal organizational regulations. Conversely, cathegory requiring operational shifts or innovative work methods record the highest behavioral resistance due to rigid bureaucratic structures. Furthermore, demographic factors such as younger age and contract status serve as crucial indicators determining higher voluntary environmental initiatives in the workplace.